The Effect of Emotions on Self-Regulated-Learning (SRL) and Story Comprehension in Emerging Readers - Buono, Stephanie; Zdravkovic, Ana; Lazic, Milan; Woodruff, Earl (Frontiers in Education, 2020)
In the early-elementary years, emerging readers experience many emotions due to the high value that is placed on the development of reading skills. If emotions are not regulated using effective learning strategies, they can negatively shape students’ experiences in and perceptions of reading, which can be detrimental to their developing reading skills. This study used automated facial expression monitoring software (FACET) to examine whether emotions affect the types of self-regulated learning (SRL) strategies students use during a narrative storytelling task and whether SRL strategies affect narrative storytelling scores. The participants were 150 emerging readers (Mage = 8, SD = 10.63, 56% girls). Results demonstrated that two emotions were related to SRL strategies; frustration was negatively related to planning and joy was positively related to monitoring. Two SRL strategies were related to narrative storytelling; planning and control were positively related to narrative storytelling scores. There was a significant indirect effect of frustration on storytelling scores through planning, indicating that planning fully mediated the effect of frustration on narrative storytelling scores. This finding suggests that although frustration has a significant negative effect on story comprehension, this relationship operates through decreased use of planning strategies. Future research should investigate pedagogical strategies to manage emotions and increase SRL strategy use during reading and literacy activities.